Navigating challenges: the impact of artificial intelligence on job satisfaction / Rosliza Md Zani, Syukriah Ali and Shakirah Mohd Saad - Md Zani, Rosliza; Ali, Syukriah; Mohd Saad, Shakirah (Universiti Teknologi MARA, Kedah, 2024)
Artificial intelligence (AI) is transforming workplaces and influencing employee satisfaction through historical foundations and current trends. The historical adoption of AI since the mid-20th century has had a dramatic impact on numerous industries, causing a comprehensive evaluation of its implications for job satisfaction (Yagnesh, 2023). Challenges connected with AI integration, such as job displacement worries rooted in previous fears of automation, exist in the present (Ivanov et al., 2020). Balancing technological advancement with employee satisfaction remains a constant challenge, thus emphasizing the importance of having a full understanding of AI's historical and contemporary impact on employee satisfaction in the shifting working environment. The coexistence of AI and human labor introduces contemporary challenges as evidenced by shifts in interpersonal dynamics and the demand for transparent decisionmaking processes (Nazareno & Schiff, 2021). The manufacturing sector is particularly impacted by the widespread adoption of automation and AI-driven technologies, potentially causing heightened job displacement anxiety among workers (Cox, 2023). The intricate relationship between AI and job satisfaction is portrayed dynamically by the historical development of AI and emerging trends. Conversely, it emphasizes the need for a comprehensive investigation that considers both historical concerns and contemporary complexities in the current work environment. Thus, this paper seeks to explore the complexities of this intersection to demonstrate the difficulties associated with implementing AI in the workplace and its significant effects on employees' overall satisfaction and well-being.